Thermo-fluid-coupled analysis and simulation of calorimeter of Experimental Advanced Superconducting Tokamak neutral beam injection system on the thermal inertia principle. (April 2017) - Tao, Ling; Hu, Chundong; Xie, Yuanlai
An efficient and accurate thermo-fluid-coupled analysis is the basis of structure design and optimization for high-heat-flux components in neutral beam injection system of Experimental Advanced Superconducting Tokamak and has an important significance of exploring the optimal structure of components and realizing the temperature control of components at a high-parameter steady-state condition. In this article, take the calorimeter in the Experimental Advanced Superconducting Tokamak–neutral beam injection system on the thermal inertia principle, for example, an accurate numerical solution method of thermo-fluid-coupled analysis based on the turbulent heat transfer is established and combined with the near-wall function model, and the working characteristics of three-dimensional calorimeter plate under different deposited beam powers are simulated and analyzed. The temperature distribution of solid structure and corresponding flow field under given cooling condition is calculated. The results obtained by the proposed method coincide well with experimental results, which validate this method. This study provides a potentially useful method for thermo-fluid-coupled analysis and structural design of other high-heat-flux components in the Experimental Advanced Superconducting Tokamak–neutral beam injection system.